2012
DOI: 10.1007/s10880-011-9279-7
|View full text |Cite
|
Sign up to set email alerts
|

Dyadic Coping Among Couples with COPD: A Pilot Study

Abstract: COPD (chronic obstructive pulmonary disease) is associated with psychological distress for patients as well as their partners. Dyadic coping can be negatively impacted by stressors. This study's objective was to compare the dyadic coping of couples in which one partner suffered from COPD with healthy couples of the same age. A total of 43 complete couples with COPD and 138 healthy couples participated in this pilot study. The surveys were sent by mail. The response rate of the COPD sample was 24.3%. In order t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…However, partners' rating of their own stress communication was rather low. Figures are similar to those reported by partners of patients with COPD in a recent study, which in turn were significantly lower than those reported by a normative comparison group of healthy couples (Meier et al 2012). On the one hand, it may be true that discussion of illness-related problems did not become rampant, with the result that stress communication can be seen as a beneficial dyadic coping strategy, having a positive influence on quality of life or couple satisfaction (Revenson et al 2005).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, partners' rating of their own stress communication was rather low. Figures are similar to those reported by partners of patients with COPD in a recent study, which in turn were significantly lower than those reported by a normative comparison group of healthy couples (Meier et al 2012). On the one hand, it may be true that discussion of illness-related problems did not become rampant, with the result that stress communication can be seen as a beneficial dyadic coping strategy, having a positive influence on quality of life or couple satisfaction (Revenson et al 2005).…”
Section: Discussionsupporting
confidence: 87%
“…As this is in line with cross-sectional results of Meier et al (2011), being able to take over tasks for the partner is an essential aspect of dyadic coping. However, partners' scores for delegated dyadic coping are relatively low compared to figures published in a previous study (Meier et al 2012). Thus, this finding may be subject to limited generalizability.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Matched control groups should also be taken into account for a better understanding of differences in dyadic coping with social stressors between significant and caregiving others of impaired versus healthy people [28]. We applied the rSMSC for the first time in an Indonesian sample while it should be discussed whether this model applies well in this.…”
Section: Discussionmentioning
confidence: 99%
“…Support comes also from studies conducted on chronic illness (Acitelli & Badr, 2005;Hagedoorn et al, 2008Naumann, 2004;Rohrbaugh et al, 2002;Meier et al, 2012), immigration stress (Falconier, Nussbeck & Bodenmann, 2013;Austin & Falconier, 2013), sexual behavior , and in cross-cultural samples (Bertoni et al, 2007;Ledermann et al, 2010) .…”
Section: Systemic-transactional Modelmentioning
confidence: 99%